Adaptation of Bakhtin's carnival characteristics in Persian "parody" based on the principles of contemporary criticism - Ahmad Goli; Yadollah Nasrollahi; Fereshteh Ahikhteh (مطالعات زبانی و بلاغی)
Content for laughter and sarcasm, whether in the frame of comedy or in the context of ridiculous works, has a long history. The experiences of the practitioners in this field have had a great impact on the general thoughts and lifestyle of the people, and in recent centuries, theorists have examined the philosophy of its operation from various angles. The most significant theorization in this field is Bakhtin's dialogism, which is based on the language play he names as heteroglossia. after the concept has been discussed in the study of novel and other discourses of social and literary satires such as "Carnival,"  "parody," and so on.‌‌ The interpretation and deconstruction of polyphonic conversational logic within the infrastructure of creative misreading and the humor in carnival discourse and parody can be conducted in terms of employing Russian Formalist notion of familiarization,  the disconnection and isolation of text from normal structure in French deconstruction and the psychological evolution of humor to creativity.The result of this descriptive study, an analysis based on library and internet sources, indicates that Persian parodies share intertextual features and borrow from polyphonic language of Carnival. These parodies are the same as literary comedies that has gone through a journey from the domain of humor to creativity with an intentional failure in the imitation of the content, language or style of serious works.